Management of chronic myeloid leukemia in the setting of pregnancy: when is leukocytapheresis appropriate? A case report and review of the literature. Issue 2 (11th December 2017) - Staley, Elizabeth M.; Simmons, Sierra C.; Feldman, Alexander Z.; Lorenz, Robin G.; Marques, Marisa B.; Williams, Lance A.; Zheng, X. Long; Pham, Huy P.
Abstract : BACKGROUND: Chronic myeloid leukemia (CML) is a common hematologic malignancy; however, its occurrence during pregnancy is unusual due to its low prevalence in females of childbearing age. There are conflicting reports of how to best manage CML in pregnancy, particularly in the setting of leukocytosis. Hemapheresis: A 30‐year‐old female was diagnosed with CML at 18 weeks' estimated gestational age. On initial presentation she reported fatigue, night sweats, and early satiety, and was found to have a white blood cell (WBC) count of 69.3 × 10 9 /L and platelet count of 366 × 10 9 /L. Her disease was managed during pregnancy using interferon‐α alone despite persistent leukocytosis. CONCLUSION: CML may be effectively managed during pregnancy, even in the setting of leukocytosis, without the application of leukocytapheresis. Management relies not only upon the coordination of drug therapy and fetal monitoring, but requires close communication between multiple medical disciplines. Leukocytapheresis has been safely performed during pregnancy and may be a suitable adjunct management strategy in pregnant patients diagnosed with CML with specific clinical presentations, such as hyperleukocytosis (WBC count > 150 × 10 9 /L) and/or symptomatic leukostasis.